Role of Fintech in Indian Banking Industries - swaranjali24, swaranjali24 (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Advancement of technology in banking sectors has enabled banks to outreach for largest financial delivery in India. With the expanding coverage day by day, customer service has come under stressed to meets its demands. Implementation of technology has revolutionised traditional banking systems by meeting the soaring demands and expectations of the customers.